Influence of Organizational Culture, Individual Characteristics, and Work Discipline on Employee Performance Inpt. Federal International Finance Bogor Branch - ismartaya ismartaya; SRM Indah Permata (Jurnal Manajemen Industri dan Logistik, 2022)
Competition in the industrial world is very tight, requiring PT. Federal International Finance Bogor West Java Branch to have the ability to compete. The progress of an industry is determined by the quality of its human resources, so employees are required to show good performance. The purpose of this study was to determine how organizational culture, individual characteristics and work discipline affect employee performance at PT. Federal International Finance Bogor Branch The method used is multiple linear regression analysis. The sample used, using the saturated sampling technique in this study, was 55 employees. The results of this study indicate that organizational culture, individual characteristics and job satisfaction have a significant influence simultaneously or partially on employee performance